A participação social no território usado: o processo de emancipação do município de Hortolândia - Kurka, Anita Burth (2008)
The research object of the present thesis is the social participation, from the perspective of used territory , as an intrinsic component of political action in the emancipation process of the city of Hortolândia São Paulo, in the period 1953 1991. The objective of the work is understanding the social participation as part of the used territory and the constitutive category of Social Work. This theoretical-methodological encounter between Geography and Social Work had the Periodization Matrix of territorial formation of Hortolândia as a basic instrument. The interpretation and description of such a matrix has identified object related events in both civil society and state, in the places of Sumaré and Hortolândia. It has been observed that the process of social participation in Sumaré and Hortolândia was promoted by the social and urban infra structure demands. An intensive and extensive policy of incentive for the installation of industries in the region resulted in an accelerated urbanization and populational growth. Government administrative actions favored primarily the interests of the industries. Social participation was molded and expressed in the form of protest acts and collective actions of social movements and communitarian and philanthropic associations, contributing to the concretization of emancipation of Hortolândia, a district of Sumaré, in 1991